Influence of Video Games on Cognitive Abilities and Intelligence - Dorja Hatlak; Andrija Bernik; Igor Tomičić (Tehnički Glasnik, 2023)
This paper gives an overview of development in research concerning the influence of video games on cognitive development and intelligence. The first part of the paper mentions three categories used by different researchers in their research: generally speaking, the development of constructs and commercial games. StarCraft is mentioned in the paper, one of the most complex strategical games of all time, and its influence on professional players in eSport. Additionally, it presents a taxonomy of strategy games compared to real world situations, such as crisis management and control. The papers indexed in Scopus and Web of Science databases are chosen for this research since they are based on the cognitive relations between the games and players. One of the conclusions is that games can influence the enhancement of cognitive abilities in both directions.